2007
DOI: 10.1007/s10459-007-9076-0
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in the selection of applicants for medical school

Abstract: Decisions about admissions to medical school are based on assessments of the applicants' cognitive achievements and non-cognitive traits. Admission criteria are expected to be fair, transparent, evidence-based and legally defensible. However, unlike cognitive criteria, which are highly reliable and moderately valid, the reliability and validity of the non-cognitive criteria are low or uncertain. Their uncertain predictive value is due not only to their limited validity, but also to the unknown prevalence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 56 publications
4
81
1
5
Order By: Relevance
“…With regard to the selection process of medical students, our research provides useful knowledge about the additional impact of non-cognitive factors (on top of cognitive factors). As argued in the literature (Benbassat & Baumal, 2007;lambe & Bristow, 2011;O'neill, Hartvigsen, Wallstedt, Korsholm, & Eika, 2011), the assessment of non-cognitive factors may lead to a better self-selection of the medical applicants. Providing objective and reliable information to the applicants about their working behaviours (compared to the ones of medical students) will enable them to make a well-considered study decision.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…With regard to the selection process of medical students, our research provides useful knowledge about the additional impact of non-cognitive factors (on top of cognitive factors). As argued in the literature (Benbassat & Baumal, 2007;lambe & Bristow, 2011;O'neill, Hartvigsen, Wallstedt, Korsholm, & Eika, 2011), the assessment of non-cognitive factors may lead to a better self-selection of the medical applicants. Providing objective and reliable information to the applicants about their working behaviours (compared to the ones of medical students) will enable them to make a well-considered study decision.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In their defence, proponents of widening access suggest that it does not weaken the medical profession, 6,15 rather it enhances it. Clearly, this is a need for joined-up initiatives encompassing an understanding of students' motivation for choice of career and professional aspirations, future workforce needs and possible policies on admission, to better ensure effective workforces in medicine and dentistry and facilitate the most appropriate 42 however, we live in a fast changing world and medicine and dentistry of the future may require different attributes; for example, it will be interesting to observe if the anticipated changes in skill mix in dentistry, with dentists assuming more of a leadership role, will have an infl uence in years to come. 28 Given the fi ndings of this paper, it is important to note that with little formal emphasis on 'widening access', 43 dentistry is consistently appearing to attract Asians and more so than medicine.…”
Section: Admissionsmentioning
confidence: 99%
“…Everywhere there have been calls for increases both in number and diversity of health care practitioners in the workforce 2 . It has been suggested that a review of the medical school admission process should be done to turn it more effective and representative of Society's needs 1,[3][4][5] , since the future physician workforce is shaped both by the admission process and medical training. Although researchers have accomplished considerable amount of work in medical education, there are relatively few studies about medical school admission process of the early 21 st century.…”
Section: Introductionmentioning
confidence: 99%
“…The United Kingdom Clinical Aptitude Test in the United Kingdom, the Medical College Admission Test (MCAT) and the Scholastic Aptitude Test (SAT) in the United States are examples of cognitive tests. The second group (i.e., non-cognitive) considers interviews, discussions of problems in groups, letters of recommendation, and performance on personality tests, such as the Multiple Mini Interviews (MMI), among others 3 . A recent study of medical school admission process in the USA suggests that several aspects of medical school admission process remain unchanged since the mid-1980s, whereas others went through major modifications 1 .…”
Section: Introductionmentioning
confidence: 99%